Evaluation of urine glutathione peroxidase 4 in cats with chronic kidney disease - Hsu, Wei-Li; Huang, Sheng-Hui; Hseu, Zeng-Yei; Wu, Vin-Cent; Chen, Ying-Hao; Lee, Ya-Jane (Frontiers in Veterinary Science, 2026)
IntroductionFerroptosis is a distinct form of regulated cell death characterized by iron-dependent lipid peroxidation that damages cellular membranes and leads to the end of a cell’s life. Glutathione peroxidase 4 (GPX4), the only enzyme capable of the reduction of lipid peroxidation products within cells, is a key regulator of this process.AimsThe role of GPX4 in feline chronic kidney disease (CKD) has not been previously investigated. This study aims to determine whether urine GPX4 levels are associated with CKD severity in cats and to assess their potential as a progression biomarker.MethodsUrine GPX4 levels were measured using a commercial feline ELISA kit. The urine-GPX4-to-creatinine ratio (UGCR) was calculated. Fifteen healthy cats, 61 cats with CKD, and six cats with acute-on-chronic kidney disease (ACKD) were included in the study.ResultsCompared with the control group (urine GPX4, median [IQR]: 25.21 [18.99–26.91]; UGCR: 0.072 [0.057–0.101] × 10−4) and the early-stage CKD group (urine GPX4: 24.31 [22.00–24.07]; UGCR: 0.134 [0.070–0.260] × 10−4), cats with late-stage CKD showed significantly higher levels of urine GPX4 (26.89 [25.11–31.66]; p = 0.011) and UGCR values (0.271 [0.197–0.457] × 10−4; p < 0.001). Within the CKD subgroups, UGCR was significantly higher in cats with proteinuria, hypertension, anemia, and those receiving iron supplementation (all p < 0.003). Serum creatinine levels and WBC counts were identified as independent variables that were correlated with UGCR. Cats in the CKD progression group had higher UGCR than non-progressors, and an elevated UGCR was associated with an increased risk of CKD progression (hazard ratio [HR], 1.75; 95% CI, 1.20–2.54; p = 0.003).Conclusion and clinical importanceUGCR increased with the severity of CKD and was significantly associated with serum creatinine concentration and disease progression. Urine GPX4 may thus serve as a novel biomarker for monitoring renal deterioration and progression in cats with CKD.